Identification of a novel p300-specific-associating protein, PRS1 (phosphoribosylpyrophosphate synthetase subunit 1) - Kaida, Atsushi (Portland Press Ltd., 2005)
CBP [CREB (cAMP-response-element-binding protein)-binding protein] and p300 play critical roles in transcriptional co-activation, cell differentiation, proliferation and apoptosis. Multiple transcription factors associate with CBP/p300. With the exception of the SYT oncoprotein, no proteins have been identified that specifically associate with p300, but not CBP. In the present study, we isolated a novel p300-associated protein for which no interaction with CBP was observed by GST (glutathione S-transferase) pull-down assay using Jurkat cell lysates metabolically labelled with [(35)S]methionine. This protein bound the KIX (kinase-inducible) domain of p300. Following resolution by two-dimensional acrylamide gel electrophoresis, we identified the KIX-domain-bound protein by MS analysis as PRS1 (phosphoribosylpyrophosphate synthetase subunit 1), a protein essential for nucleoside biosynthesis. This is the first report to demonstrate the existence of a p300 KIX-domain-specific-interacting protein that does not interact with CBP. Thus p300 may play a role in the regulation of DNA synthesis through interactions with PRS1.